Safeguarding banana diversity at the Bioversity International Musa Germplasm Transit Centre - Bioversity International (Bioversity International, 2017)
The Bioversity International Musa Germplasm Transit Centre (ITC) is home to the world’s largest collection of banana diversity. Its mission? To contribute to the secure long-term conservation of the entire banana genepool and hold the collection in trust for the benefit of current and future generations under the auspices of the Food and Agriculture Organization of the UN. Founded in 1985, the ITC is managed by Bioversity International and hosted at the Katholieke Universiteit Leuven, Belgium. The collection contains more than 1,500 accessions of edible and wild species of banana, and the collection continues to grow as new specimens are collected in the crop’s centres of diversity in South-east Asia, and East and West Africa.